METODE PAIN RELIEF DI TPMB BANDUNG RAYA: SEBUAH STUDI DESKRIPTIF - Nurchasanah, Yuni; Mulyati, Sri (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, 2025)
The physiological and psychological changes that occur during childbirth often result in maternal discomfort, with pain being a significant factor. Labor pain is frequently perceived as a distressing experience for women. This fear and discomfort has an impact on the slow progress of the labor process and gives a negative experience to the birth. This study aimed to examine the management of labor pain during the first stage of labor in private midwifery practice in The Bandung area. This research employed a descriptive method using a survey approach, wherein questionnaires were distributed to midwife respondents with minimal background Diploma III in midwifery, perform maternity service and working in independent midwifery practices across Bandung City, Cimahi City, Bandung Regency, and West Bandung Regency during October 2023. The collected data were then analyzed using univariate analysis, presented in the form of frequency distributions. The research results contained data originating from 89 midwife-independent practice in the Bandung area. Data collection revealed that 87 independent midwifery practices utilized various pain relief methods, including massage, birth balls, aromatherapy, warm and cold compresses, hypnotherapy, acupuncture, rebozo techniques, distraction, reflexology, and water immersion. These practices allow birthing mothers to select their preferred pain relief method. The study concludes that nearly all private practice midwives in the greater Bandung area implement pain management techniques as part of care during the first stage of labor.